FPGA in hardware description language based digital clock alarm system with 24-hr format - Sayudzi, Mohd Faris Izzwan Mohd; Hamzah, Irni Hamiza; Malik, Azman Ab; Idris, Mohaiyedin; Soh, Zainal Hisham Che; Rahim, Alhan Farhanah Abd; Hadis, Nor Shahanim Mohamad (International Journal of Reconfigurable and Embedded Systems (IJRES), 2024)
Currently, digital clock adapts microprocessor or microcontroller system. Performance of speed and reconfigurability issue become a main concern in digital clocks. New additional feature may be introduced in digital clocks in the future. Field programmable gate array (FPGA) offer better performance of speed and reconfiguration features. Based on these advantages, it is essential to study or explore the digital clock with FPGA design. The objective in this study is to create a hardware description language (HDL)- based digital clock with alarm system and implement it onto the Altera DE2- 115 board. Using Verilog HDL language in Quartus Prime 20.1 Lite Edition software, all submodule components is developed and being test benched using ModelSim-Altera Starter Edition 13.1 to ensure the correct functionality. Then all inputs and outputs will be assigned through pin assignment in the software. For verification purpose, it will be downloaded to the Altera DE2-115 board. In conclusion, the file has been successfully implemented to the board and the digital clock with alarm is fully functional as expected. This was proved by the alarm signal, time adjustment and display of the three-display mode which is clock, alarm, and input where each mode carries their own functions as expected.